Pengaruh Kepemimpinan Transformasional Motivasi Kinerja Guru Madrasah Tsanawiyah Negeri dan Swasta Kecamatan Cipayung - Nurhaeni Nurhaeni; I Dewa Ketut Kerta Widana; Sri Yanthy Yosepha (Yayasan Madinah Al-Aziziyah, 2026)
This study aims to analyze the influence of transformational leadership, work discipline, and work motivation on the performance of teachers at both public and private Madrasah Tsanawiyah (Madrasah Tsanawiyah) in Cipayung District, East Jakarta. The background of this research is based on the phenomenon of less-than-optimal teacher performance, which is suspected to be influenced by a transactional leadership style, weak work discipline, and fluctuating work motivation. This research uses a quantitative method with a survey approach. The population was 115 teachers from three madrasahs, and a sample of 89 respondents was determined using the Slovin formula with a simple random sampling technique. Data was collected through a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis techniques used path analysis with the help of SPSS software. The results of this study are analysis to prove that (1) transformational leadership has a direct positive effect on teacher performance, (2) work discipline has a direct positive effect on teacher performance, (3) work motivation has a direct positive effect on teacher performance, (4) transformational leadership has a direct positive effect on work discipline, (5) transformational leadership has a direct positive effect on work motivation, (6) work discipline has a direct positive effect on work motivation, and (7) transformational leadership has an indirect positive effect on teacher performance through work motivation. These findings confirm the importance of synergy between inspirational leadership, consistent discipline, and strong motivation in creating superior and sustainable teacher performance.